ChemInform Abstract: Click Chemistry with 2‐Ethynyl‐4, 5, 6, 7‐tetrahydroindoles: Towards Functionalized Tetrahydroindole—Triazole Ensembles. Issue 26 (6th June 2013) - Sobenina, Lyubov N.; Tomilin, Denis N.; Ushakov, Igor A.; Mikhaleva, Albina I.; Ma, J. Sh.; Yang, G.; Trofimov, Boris A.
Abstract 1, 3‐Dipolar cycloaddition of the azide anion with internal alkynes of type (I) bearing an acyl or ester moiety offers a direct synthesis of the target scaffolds under very mild conditions.